ANALISIS PERBANDINGAN KINERJA KEUANGAN RISK-BASED BANK RATING PADA BANK UMUM SYARIAH DAN BANK UMUM KONVENSIONAL DI INDONESIA PERIODE 2016-2020: COMPARATIVE ANALYSIS OF RBBR FINANCIAL PERFORMANCE IN BUS AND BUK IN INDONESIA FOR THE 2016-2020 PERIOD - Niken Hustilah; Yudi Yudi; Riski Hernando (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This research was conducted with the aim of knowing the financial performance and soundness of Islamic Commercial Banks and Conventional Commercial Banks using the RBBR (Risk Based-Bank Rating) method with aspects of Risk Profile (NPL/NPF, and LDR/FDR), Good Corporate Governance (GCG), Earnings (ROA, ROE, and BOPO), and Capital (CAR). This research is a comparative quantitative study that was analyzed using the Independent Sample T-Test and Mann Whitney. The results of this study show that there are significant differences in the financial performance of Islamic Commercial Banks and Conventional Commercial Banks in terms of the NPL/NPF ratio, while for the ratio of LDR/FDR, GCG, ROA, ROE, BOPO, and CAR there is no significant difference in the financial performance of Islamic Commercial Banks and Conventional Commercial Banks. The soundness level of Islamic commercial banks is in a better condition than conventional commercial banks in the ratio of LDR/FDR, while the NPL/NPF, ROA, ROE, and BOPO ratios of conventional commercial banks are in better condition than Islamic commercial banks. GCG Aspect and CAR are in the same good health condition as Islamic Commercial Banks and Conventional Commercial Banks